Quantum state tomography of molecules by ultrafast diffraction - Zhang, Ming; Zhang, Shuqiao; Xiong, Yanwei; Zhang, Hankai; Ischenko, Anatoly A.; Vendrell, Oriol; Dong, Xiaolong; Mu, Xiangxu; Centurion, Martin; Xu, Haitan; Miller, R. J. Dwayne; Li, Zheng (Nature Communications, 2021)
Ultrafast electron diffraction and time-resolved serial crystallography are the basis of the ongoing revolution in capturing at the atomic level of detail the structural dynamics of molecules. However, most experiments capture only the probability density of the nuclear wavepackets to determine the time-dependent molecular structures, while the full quantum state has not been accessed. Here, we introduce a framework for the preparation and ultrafast coherent diffraction from rotational wave packets of molecules, and we establish a new variant of quantum state tomography for ultrafast electron diffraction to characterize the molecular quantum states. The ability to reconstruct the density matrix, which encodes the amplitude and phase of the wavepacket, for molecules of arbitrary degrees of freedom, will enable the reconstruction of a quantum molecular movie from experimental x-ray or electron diffraction data. Ultrafast diffraction is fundamental in capturing the structural dynamics of molecules. Here, the authors establish a variant of quantum state tomography for arbitrary degrees of freedom to characterize the molecular quantum states, which will enable the reconstruction of a quantum molecular movie from diffraction data.
Gesehen am 24.09.2021